Modulating Neurological Complications of Emerging Infectious Diseases: Mechanistic Approaches to Candidate Phytochemicals - Echeverria-Morgado, J (Frontiers Media S.A., 2021)
Growing studies are revealing the critical manifestations of influenza, dengue virus (DENV) infection, Zika virus (ZIKV) disease, and Ebola virus disease (EVD) as emerging infectious diseases. However, their corresponding mechanisms of major complications headed for neuronal dysfunction are not entirely understood. From the mechanistic point of view, inflammatory/oxidative mediators are activated during emerging infectious diseases towards less cell migration, neurogenesis impairment, and neuronal death. Accordingly, the virus life cycle and associated enzymes, as well as host receptors, cytokine storm, and multiple signaling mediators, are the leading players of emerging infectious diseases. Consequently, chemokines, interleukins, interferons, carbohydrate molecules, toll-like receptors (TLRs), and tyrosine kinases are leading orchestrates of peripheral and central complications which are in near interconnections. Some of the resulting neuronal manifestations have attracted much attention, including inflammatory polyneuropathy, encephalopathy, meningitis, myelitis, stroke, Guillain-Barré syndrome (GBS), radiculomyelitis, meningoencephalitis, memory loss, headaches, cranial nerve abnormalities, tremor, and seizure. The complex pathophysiological mechanism behind the aforementioned complications urges the need for finding multi-target agents with higher efficacy and lower side effects. In recent decades, the natural kingdom has been highlighted as promising neuroprotective natural products in modulating several dysregulated signaling pathways/mediators. The present study provides neuronal manifestations of some emerging infectious diseases and underlying pathophysiological mechanisms. Besides, a mechanistic-based strategy is developed to introduce candidate natural products as promising multi-target agents in combating major dysregulated pathways towards neuroprotection in influenza, DENV infection, ZIKV disease, and EVD. Copyright © 2021 Fakhri, Mohammadi Pour, Piri, Farzaei and Echeverría.